Outcomes of skin surgery - Colver, Graham (Informa Healthcare, 2008)
There is a great need for a visual resource to document, with clarity, the possible outcomes of surgery, including side effects and complications, and how these outcomes vary from individual to individual. Using a straightforward approach, Outcomes of Skin Surgery: A Concise Visual Aid is an easy-to-consult and highly illustrated reference for surgeons and patients alike. This text takes a major step forward in establishing a realistic basis for the decision-making process during a consultation.